2009
DOI: 10.1021/jp8112123
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Energy Migration in an Organic Dendrimer Macromolecule for Sensory Signal Amplification

Abstract: The issue of macromolecular exciton delocalization length and fluorescence sensing of energetic materials is investigated and modeled from results of nonlinear optical and time-resolved spectroscopy. By using two- and three-photon absorption techniques the fluorescence quenching effects of an organic dendrimer for sensing TNT were carried out. The Stern-Volmer plots for the set of dendrimers were examined and a large quenching constant for the dendrimer G4 was obtained (1400 M(-1)). The quenching constant was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 38 publications
1
47
1
Order By: Relevance
“…Dendrimers are represented by multiple subclasses depending on their chemical composition—thus, the subclass of phosphorus dendrimers is defined by the presence of at least one phosphorus atom at each branching point. Branched moieties can be broadly modified to shape the key biochemical properties of dendrimers depending on the desired application, such as surface charge, peptide‐based targeting, or fluorescence when fluorophores are incorporated in their structure . The presence of numerous surface groups (charged or modified as necessary) and a hydrophobic core allows for a high drug payload and multifunctionality, conferring also the ability to transport therapeutic cargos across various cell membranes or biological barriers via cellular internalization .…”
Section: Introductionmentioning
confidence: 99%
“…Dendrimers are represented by multiple subclasses depending on their chemical composition—thus, the subclass of phosphorus dendrimers is defined by the presence of at least one phosphorus atom at each branching point. Branched moieties can be broadly modified to shape the key biochemical properties of dendrimers depending on the desired application, such as surface charge, peptide‐based targeting, or fluorescence when fluorophores are incorporated in their structure . The presence of numerous surface groups (charged or modified as necessary) and a hydrophobic core allows for a high drug payload and multifunctionality, conferring also the ability to transport therapeutic cargos across various cell membranes or biological barriers via cellular internalization .…”
Section: Introductionmentioning
confidence: 99%
“…57 Due to the large two-photon absorption cross-sections of the high-generation dendrimers, fluorescence quenching could be stimulated under near-IR irradiation. 56,57 The dynamics of fluorescence anisotropy decay on the picosecond timescale revealed that closer packing of the surface groups in the higher generation dendrimers allowed effective migration of the excitons around the dendrimer surface to a quenching site. 56 This amplified the fluorescence quenching effect for higher generations in an analogous manner to the molecular wire effect of amplifying fluorescent polymers.…”
Section: Dendrimersmentioning
confidence: 99%
“…56,57 The dynamics of fluorescence anisotropy decay on the picosecond timescale revealed that closer packing of the surface groups in the higher generation dendrimers allowed effective migration of the excitons around the dendrimer surface to a quenching site. 56 This amplified the fluorescence quenching effect for higher generations in an analogous manner to the molecular wire effect of amplifying fluorescent polymers. It was hypothesised that porous films of these materials would make effective solid state sensors for explosive vapours but at the time of writing this had not been reported.…”
Section: Dendrimersmentioning
confidence: 99%
See 1 more Smart Citation
“…A larger reflects a stronger fluorescence quenching response. This relatively straightforward method has been used to investigate the quenching ability of a wide range of explosive analytes and taggants with a variety of materials such as small molecules 50,51 , dendrimers 52,53 , functionalized nanoparticles 54,55 , and polymers 49,56 . Solution quenching measurements of these materials, using paraquat as the analyte, yielded values that were 2.6 to 65 times larger than that of the monomeric receptor 3.1 (1630 M -1 ).…”
Section: Introductionmentioning
confidence: 99%